Body Posture Modulates Action Perception - Zimmermann, Marius (J Neurosci, 2013)
Recent studies have highlighted cognitive and neural similarities between planning and perceiving actions. Given that action planning involves a simulation of potential action plans that depends on the actor's body posture, we reasoned that perceiving actions may also be influenced by one's body posture. Here, we test whether and how this influence occurs by measuring behavioral and cerebral (fMRI) responses in human participants predicting goals of observed actions, while manipulating postural congruency between their own body posture and postures of the observed agents. Behaviorally, predicting action goals is facilitated when the body posture of the observer matches the posture achieved by the observed agent at the end of his action (action's goal posture). Cerebrally, this perceptual postural congruency effect modulates activity in a portion of the left intraparietal sulcus that has previously been shown to be involved in updating neural representations of one's own limb posture during action planning. This intraparietal area showed stronger responses when the goal posture of the observed action did not match the current body posture of the observer. These results add two novel elements to the notion that perceiving actions relies on the same predictive mechanism as planning actions. First, the predictions implemented by this mechanism are based on the current physical configuration of the body. Second, during both action planning and action observation, these predictions pertain to the goal state of the action.